Tet family proteins and 5-hydroxymethylcytosine in development and disease - Tan, Li (Company of Biologists, 2012)
Over the past few decades, DNA methylation at the 5-position of cytosine (5-methylcytosine, 5mC) has emerged as an important epigenetic modification that plays essential roles in development, aging and disease. However, the mechanisms controlling 5mC dynamics remain elusive. Recent studies have shown that ten-eleven translocation (Tet) proteins can catalyze 5mC oxidation and generate 5mC derivatives, including 5-hydroxymethylcytosine (5hmC). The exciting discovery of these novel 5mC derivatives has begun to shed light on the dynamic nature of 5mC, and emerging evidence has shown that Tet family proteins and 5hmC are involved in normal development as well as in many diseases. In this Primer we provide an overview of the role of Tet family proteins and 5hmC in development and cancer.